National innovation system as a condition for the improvement of the competitiveness of the Ukrainian economy - Дмитренко, Александр Владимирович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The article considers the growth of the competitiveness of the country’s economy. The main causes of the development of the national innovation system as a condition for the growth of the competitiveness of the national economy were identified and the main directions of innovation policy were shown. The basic factors of the development of the innovation economy were determined and grouped together. There are three areas outlined: technological development of the society; globalization of the world economy; intensification of the country’s scientific potential. Comparison with post-socialist countries of Eastern Europe allowed identifying common basic problems of reforming the scientific sphere. These include: a dominant funding from the state budget, which covers only wage and utility costs of scientific institutions; weak development of innovation infrastructure and the collapse of the expectations for changes in the scientific sector through the introduction of multisource funding model peculiar to the countries with developed market economies.By assessing the level of innovative activity in the ranking of the World Intellectual Property Organization (WIPO) there was created an innovative profile of Ukraine as a country with significant potential for innovation without a significant impact on the economy. Innovative profile enables to assess the advantages and disadvantages of innovative activity in the country.The directions of strategic development of high technology industry were determined. The first direction is restoration and organization of high-tech industries, based on Ukrainian innovative technologies that are competitive on the world market. The second direction is import substitution of foreign domestic high-tech products on the basis of the disclosure of their uniqueness (against foreign analogues) at a lower cost. The third direction is restoration of the expanded reproduction of high-tech means of production. The fourth one is development of structure-oriented investment policy.